Disgust sensitivity in the first trimester predicts anxiety levels in advanced pregnancy - Takács, Lea; Ullmann, Jana; Dlouhá, Daniela; Monk, Catherine; Nouzová, Kamila; Hrbáčková, Hana; Kaňková, Šárka (Midwifery, 2025)
PROBLEM: Disgust contributes to anxiety-based psychopathology, and in turn, anxiety increases disgust proneness. BACKGROUND: Disgust and anxiety undergo significant changes in pregnancy, but no previous study has examined their longitudinal associations in this time period. AIM: This prospective longitudinal study aimed to identify longitudinal associations between disgust sensitivity and state anxiety across the three trimesters of pregnancy, while exploring the directionality of the effect between those two variables. METHODS: At each trimester of pregnancy, the pregnant women (n = 261) completed the Disgust Scale-Revised (DS-R), the Pathogen disgust domain of the Three Domains of Disgust Scale (TDDS), and the State-Trait Anxiety Inventory. A path analysis (structural equation model) was used to assess cross-lagged effects between disgust sensitivity and state anxiety across the three pregnancy trimesters. FINDINGS: We found significant cross-lagged associations between disgust and anxiety such that higher disgust (overall DS-R score, Core disgust subscale of DS-R and Pathogen disgust domain of TDDS) in the first trimester predicted greater anxiety in the third. No significant cross-lagged associations were found between Animal-reminder or Contamination disgust subscales of DS-R and state anxiety. State anxiety did not predict disgust sensitivity at any time point. DISCUSSION: Our results indicate a unidirectional association between disgust sensitivity and state anxiety in pregnant women such that disgust sensitivity in early pregnancy predicts state anxiety in late pregnancy, but anxiety does not predict disgust sensitivity at any time point. CONCLUSION: Assessing disgust in early pregnancy could help to identify women at risk of higher anxiety levels in advanced pregnancy.
Keywords: Cross-lagged path model; dospělí; trimestry těhotenství; průzkumy a dotazníky; Female; úzkost; Adult; ženské pohlaví; Pregnant People; Surveys and Questionnaires; longitudinální studie; prenatální diagnóza; Predictive Value of Tests; prediktivní hodnota testů; COVID-19 pandemic; lidé; State anxiety; těhotenství; Prenatal Diagnosis; analýza latentních tříd; Anxiety; Emotion; Longitudinal; odpor; prospektivní studie; těhotné ženy; Prospective Studies; Latent Class Analysis; komplikace těhotenství; Pregnancy Complications; Pregnancy; Pregnancy Trimesters; Longitudinal Studies; Disgust; Humans